COMPUTER GAMES AS HOMEWORK: How to delight and instruct - Dormann, C.; Fiset, J.-P.; Caquard, S.; Woods, B.; Hadziomerovic, A.; Whitworth, E.; Hayes, A.; Biddle, R. (Robert) (2005)
We are interested in exploring how entertainment in games can be combined with educational goals to make a compelling experience. In this paper we present our design study for the development of a mod game, Antarctic NWN. We first present the background for the game, objectives, and then discuss the gameplay o f Antarctic NWN. We then explore issues that influence the design of a gripping game. One important issue is the relation between reality, simulation and game word. Then we focus on enhancing emotional involvement. Emotion is especially relevant to role-play game as it draws players into the story, and supports aesthetic understanding. We also look more specifically at the role of humour in this context. Humour enhanceslearning as well as providing a more pleasurable experience. In our quest to understand how games can both delight and instruct, we review the environment in which our game might be played, within the classroom or as family entertainment and describe different scenarios of use.